The Role of Demographic Variables on Medical Tourists\' Viewpoints about Service Quality of Hospitals - Alireza Jabbari; Maryam Gholami; Zahra Kavosi; Parisa Chamanpara (Tehran University of Medical Sciences, 2016)
Background: The subjectschr('39') demographic characteristics are factors influencing their viewpoints about healthcare quality and have a positive association with the clients' satisfaction. This study aimed at investigating the role of demographic variables on medical touristschr('39') viewpoints about service quality of hospitals in Shiraz. Materials and Methods: This descriptive-analytical and cross-sectional study was conducted on 200 foreign patients who referred to Shiraz hospitals during the first six months of 2013. Data collection tool was a questionnaire consisting of two parts. In the first part, medical touristschr('39') information was collected and in the second part, their expectations and perceptions of services quality were measured using adapted SERVQUAL scale. The validity was checked out by experts and reliability confirmed by Cronbach's Alpha test for expectations and perceptions separately (90% and 89%).  Finally, data analyzed through SPSS v.16 software using independent t-test and ANOVA. Result: According to the results, the mean score of the quality gap was estimated -0.26 for people over the age of 50 years, as it was lower than other groups. Also, the lowest total values of this quantity were related to the individuals with low level of literacy and those who stayed less than 7 days for treatment which were estimated -0.32 and -0.36 respectively. In addition, based on statistically significant dimensions, married tourists, people from Oman and those who had received eye surgery had lower gap mean score than the other patients as their total values were estimated -0.42, -0.21 and -0.22, respectively. Conclusion: In order to develop the medical tourism industry, the demographic characteristics of the subjects should be considered in policy making and service design which can be result in majority satisfaction.